Abilities and Difficulties of Ninth-Grade Students in Solving Geometry Transformation Problems - Trisna, Tasya Aprilla; Ikhsan, M; Elizar, Elizar (Jurnal Pendidikan MIPA, 2022)
Geometry is one of the challenging subjects for students. This study aimed to determine the ability of students to solve geometric transformation problems, the difficulties they experienced, and the causes. This research employed a mixed method with a sequential explanatory design. Eight Year 9 students were the subjects of this study. Data were collected through tests and interviews. The data were analyzed quantitatively, followed by qualitative analysis involving reducing data, presenting data, and concluding. The results indicated that the student's ability to solve geometric transformation problems was moderate. Students found it difficult to solve geometric transformation problems. The student's difficulties included determining the translation when a starting point and an image point were given and determining the image of a point/curve by a transformation. Students had not fully mastered the schemes in the geometric transformation, were not proficient in using formulas, and were not precise in their calculations.Keywords: students’ difficulty, transformation, translation, rotation, dilatation.DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1724-1737